2007
DOI: 10.1021/pr060433m
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression Profile in the Intestinal Epithelium from Patients with Inflammatory Bowel Disease

Abstract: The loss of intestinal epithelial cell (IEC) function is a critical component in the initiation and perpetuation of chronic intestinal inflammation in the genetically susceptible host. We applied proteome analysis (PA) to characterize changes in the protein expression profile of primary IEC from patients with Crohn's disease (CD) and ulcerative colitis (UC). Surgical specimens from 18 patients with active CD (N = 6), UC (N = 6), and colonic cancer (N = 6) were used to purify primary IEC from ileal and colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 74 publications
5
79
0
1
Order By: Relevance
“…Employing a similar rationale, direct sampling of diseased tissue in IBD (a far simpler task compared to other diseases due to routine endoscopic biopsies) has been utilised for proteomic experiments (Table 2). Shkoda et al [33] reported the first proteomic study of intestinal tissue, identifying nine statistically significant proteins delineating inflamed IBD tissue from noninflamed controls. Furthermore, 40 proteins were further detected between inflamed and noninflamed UC tissue, although only two pairs of patient samples were analysed.…”
Section: Pre-clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing a similar rationale, direct sampling of diseased tissue in IBD (a far simpler task compared to other diseases due to routine endoscopic biopsies) has been utilised for proteomic experiments (Table 2). Shkoda et al [33] reported the first proteomic study of intestinal tissue, identifying nine statistically significant proteins delineating inflamed IBD tissue from noninflamed controls. Furthermore, 40 proteins were further detected between inflamed and noninflamed UC tissue, although only two pairs of patient samples were analysed.…”
Section: Pre-clinical Presentationmentioning
confidence: 99%
“…This issue holds true across the aforementioned studies in IBD as out of 19 biosample based discovery experiments, 8 studies used ≤ 6 cases and controls [33,34,38,5659] . In an effort to address this issue, Skates et al [55] designed a statistical model that estimates the statistical power of discovery and verification studies in tissue and plasma.…”
Section: Current Limitationsmentioning
confidence: 99%
“…4 In addition, it is known that enterocytes from patients with IBD show distinct differences in protein expression profile. 5 The distinction between UC and CD is made based on clinical, endoscopic, radiologic, and pathologic features. 6 However, for about 15 to 20% of the patients it is not possible to classify them into either one of the IBD forms, with the result that diagnostics and therapy cannot be given, as requested, to these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activation of nuclear factor of activated T cell (NFAT), and ectopic expression of tumor rejection antigen 1 and poliovirus receptor related protein 1 were detected in the UCaffected colonic mucosa. Comparison with colonic mucosal proteins between UC and CD revealed their specific characters of UC and common features to IBD (25)(26)(27). Intestinal epithelial cells (IECs) from patients with UC, CD, and colon cancer, analyzed by 2DE and MALDI-TOF/MS, showed 21 protein spots with at least 2-fold change between inflamed tissue from the IBD (UC and CD) patients and non-inflamed tissue from the patients with colonic cancer (25).…”
Section: Proteomic Analyses Of Colonic Mucosa From Ucmentioning
confidence: 99%
“…Comparison with colonic mucosal proteins between UC and CD revealed their specific characters of UC and common features to IBD (25)(26)(27). Intestinal epithelial cells (IECs) from patients with UC, CD, and colon cancer, analyzed by 2DE and MALDI-TOF/MS, showed 21 protein spots with at least 2-fold change between inflamed tissue from the IBD (UC and CD) patients and non-inflamed tissue from the patients with colonic cancer (25). The identified proteins were functionally related to signal transduction, stress response, and energy metabolism.…”
Section: Proteomic Analyses Of Colonic Mucosa From Ucmentioning
confidence: 99%